Discrete Element Modeling of Permanent Deformation Accumulation in Railroad Ballast Considering Particle Breakage - Dahal, Beema; Mishra, Debakanta (Frontiers in Built Environment, 2020)
Particle shape and mineralogy have been found to greatly affect railroad ballast response under train loading. In this research effort, the effect of particle breakage on ballast permanent deformation behavior was studied using the Discrete Element Method (DEM). Real ballast particle shapes were digitized using an inexpensive imaging tool, and agglomerates of spheres were used to regenerate those complex shapes. Particle crushing tests were carried out in the laboratory, and discrete element models simulating the crushing test were calibrated based on the laboratory test results. Model parameters established through this calibration process were subsequently used to study the permanent deformation response of ballast layers comprising complex-shaped breakable ballast particles under repeated loading. The effect of particle shape was studied by comparing the permanent deformation behavior for ballast layers comprising simplified ellipsoid particles to those comprising the complex-shaped particles simulated using agglomerates of spheres. The simulation results clearly highlighted the significance of particle breakage in ballast permanent deformation accumulation under cyclic loading. Most particle breakage was observed to occur under the initial load cycles, which also corresponded to the highest rate of permanent strain accumulation. The particle breakage as well as the rate of strain accumulation gradually decreased with increasing load cycles.